Several Parameters Influencing Wine Production from Mangrove Apple (Sonneratia ovata) Fruit - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
The ripe mangrove apple is a potential source of natural antioxidants owing to its significant antioxidant activities. Phytochemical analysis of fruit extract revealed the presence of carbohydrate, protein, flavonoid and phenolic compounds. It can enhance the capability of antioxidant human body and therefore reduce the risk of chronic diseases. It is sweet in taste and usually consumed fresh or made into juice. There is limited study mentioning to processing of this functional fruit. Therefore we explored a wine fermentation from mangrove apple (Sonneratia ovata) fruit by focusing on the effect of different variables such as sugar supplementation, innoculum size, fermentation temperature in the primary fermentation, and fermentation time and temperature in the maturation to mangrove apple (Sonneratia ovata) wine quality (%v/v alcohol; g/l titratable acidity; oBrix residual sugar; sensory score). Our results proved that the primary fermentation should be conducted with 12% sugar ratio, 0.25% Sacchromyces cerevisiae inoculum at temperature 30.0oC in 15 days. The maturation was adequate in 10.0oC for 3 weeks to get a pleasant flavor and aroma. Mangrove apple (Sonneratia ovata) wine also evaluated the antioxidant capacity and total phenolic content. Mangrove apple (Sonneratia ovata) wine could be considered as a healthy source of antioxidants and phenolics ideal for daily consumption.Keywords: Mangrove apple (Sonneratia ovata), Wine, fermentation, Sacchromyces cerevisiae, Antioxidant, Phenolic.